Optimizing production in the packaging process of a dressing and ground company through the lean approach - Valencia Vasquez, Jems German (2024)
This proposal aims to improve the efficiency of the packaging process of a company specialized in seasonings and ground foods through the application of the Lean Manufacturing approach. To carry out this study, data was collected from a Peruvian company, which was evaluated using a simulated validation model in the Arena version 16.1 program. This process included the participation of experts in the relevant areas, ensuring significant results for potential implementation. The results obtained indicated a significant reduction from 7.5% to 0.08% in the generation of defective products per production. In addition, production times were reduced in tasks related to the packaging line of one of its products. These findings allowed us to conclude that the simulation model is highly replicable in various production lines of the company. In comparison with other related studies, it stands out that the implementation of Lean Manufacturing tools provides the possibility of adequate coverage in certain tasks in the food industry. Although there are not many studies with a reality similar to that of the context studied, this proposal offers valuable information to be replicated in other types of food industries.